Heresy and Citizenship Persecution of Heresy in Late Medieval German Cities - Smelyansky, Eugene (Studies in Medieval History and Culture, 2021)
"Heresy and Citizenship examines the anti-heretical campaigns in late-medieval Augsburg, Rothenburg ob der Tauber, Strasbourg, and other cities, in order to demonstrate how heretical presence in cities was used in ecclesiastical, political, and social conflicts between the cities and within their walls. These anti-heretical campaigns targeted Waldensians who believed in lay preaching, simplified forms of Christian worship, and apostolic poverty; groups of individuals identified as Waldensians-depending on the ecclesio-political context of each trial-underwent public penance, execution, or expulsion. In each case, the course and outcome of inquisitions reveal tensions between institutions within each city-most often between city councils and local bishops or archbishops. In such cases, competing sides used the persecution of heresy to assert their authority over others. As a result, persecution of urban Waldensians acquired meaning beyond mere correction of religious error. By placing anti-heretical campaigns of the 1390s in their socio-political and religious context, this volume also engages with studies of social and political conflict in late medieval towns by looking at the role that the exclusion of religiously and socially deviant groups played in the development of urban governments and the vision of cities as self-contained sacred communes. It will be of interest to scholars and students interested in medieval history, religious history, and the history of heresy and persecution"--